Switchable self-assembly of Prussian blue analogs nano-tiles triggered by salt stimulus. Issue 4 (8th January 2016) - Dedovets, D.; Bauduin, P.; Causse, J.; Girard, L.; Diat, O.
Abstract : We showed fully reversible, ionic strength controlled self-assembly of Prussian blue analogues nano-tiles into large superlattice structures. Abstract : Prussian blue analogs (PBAs) are materials well known for their bulk physical and (electro)-chemical properties, with an outstanding selectivity for caesium in ion exchange processes. Crystalline nano-tiles, made of copper based PBA, are produced and dispersed in water by tuning their electrostatic interactions. The shape and size of the nano-crystals are determined by combining scattering, microscopic and spectral techniques. We show here that Cu-PBA nano-tiles form planar superstructures by an edge to edge self-assembly process controlled by specific cation effect and ionic strength. Sedimentation and (re-)dispersion of the nano-tiles are found to be fully reversible. This switchable anisotropic self-assembly triggered by salt stimulus makes PBA nanocrystals potentially interesting for applications.